Crystal structure of Myotoxin-II: A myotoxic phospholipase A2 - homologue from Bothrops moojeni venom - De Azevedo, W. F. [UNESP]; Ward, R. J. [UNESP]; Lombardi, F. R. [UNESP]; Giglio, J. R.; Soares, A. M.; Fontes, M. R.M. [UNESP]; Arni, R. K. [UNESP] (My University, 1997)
The crystal structure of Myotoxin-II (MjTX-II), a Lys49 PLA2-homologue from Bothrops moojeni venom has been determined and refined at 2.0 Å to a crystallographic residual of 19.7% (Rfree=28.1%). MjTX-II is a dimer in the crystal, with the monomers in the asymmetric unit related by a two-fold symmetry axis running through the dimer interface. The dimers of MjTX-II and the Lys49 PLA2 from B. asper venom are similar, however the relative orientations of the monomers suggests a flexible dimer interface, which serves as a hinge between the two molecules.